Health problems related to working in extreme cold conditions indoors - Piedrahita, Hugo; Oksa, Juha; Malm, Christer; Rintamäki, Hannu (International Journal of Circumpolar Health, 2008)
To identify health problems among workers performing cleaning, maintenance and machine operation tasks inside cold storage rooms with temperatures between -43 degrees C and -62 degrees C in a freeze drying coffee company. STUDY DESIGN: Descriptive study. METHODS: All 24 workers working inside the cold stores participated in the study. A questionnaire about cold-related health problems and the standardized Nordic questionnaire assessing muscle complaints were completed by all exposed workers. A physical examination was performed on each worker. RESULTS: The most relevant cold-related health problem was episodic finger symptoms (50%), followed by respiratory symptoms (21%), peripheral circulation symptoms (20%), and repeated pain in the musculoskeletal system (12%). Two subjects had a previous diagnosis of Raynaud's phenomenon (RP). The prevalence of musculoskeletal complains in the neck and low back was 21% in each. CONCLUSIONS: The prevalence found for various complaints among the freeze drying coffee workers implies that the cold conditions inside cold stores may present a real risk of cold-related health problems and, due to lowered concentration level, for injuries, too. Greater efforts should be made to minimize the cold exposure by designing automation processes to prevent continuous exposure to cold during freeze drying process. In addition, improving the cold-protective clothing and guaranteeing its appropriate use will reduce health risks. Validerad; 2008; 20080408 (andbra)